IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF BERBASIS GENIALLY BELAJAR PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Ni Kadek Suartini; Nyoman Pancaria; Putu Eka Sastrika Ayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education at the Elementary School (SD) level plays a fundamental role in shaping the foundation of literacy, numeracy, and character in students. Interactive media is a tool used by teachers to deliver lesson material to students. The main benefit is that media can make the lesson message or information clearer and easier for students to understand. The approach applied in this research is the literature review, where data is collected through the analysis of literature review. Genially is a web-based platform that allows for the creation of multimedia content with interactive features such as presentations, maps, games, and animated images. Genially is a digital platform specifically created to make it easier for teachers to produce various teaching aids. Genially is an online platform designed to facilitate the creation of interactive educational content. This platform addresses the varied learning needs of students, covering visual, auditory, and kinesthetic learning styles. Genially serves as a tool for producing media that provides visual stimuli and interactive touches (clicks, hovers, transitions). The main aspects emphasized in the design are the interactivity features and visual elements. The primary goal of this research is to produce and prove the effectiveness of Genially-based IPAS learning media for 5th-grade elementary school students. The implementation of Interactive Genially Media in the IPAS (Science, Social Studies, and Environmental Education) subject is highly relevant for application in 5th grade of elementary school.